1983
DOI: 10.1139/b83-023
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic wind disturbance in an old-growth hemlock–hardwood forest, Wisconsin

Abstract: On 4 July 1977, the Flambeau River Hemlock–Hardwood Scientific Area (Sawyer County, WI) was leveled by a downburst of hurricane-force winds. This paper documents preblowdown and postblowdown composition in a 61-ha portion of a state Scientific Area. Total stand basal area after the blowdown was reduced to 6% of prestorm levels. Total seedling density increased greatly following the blowdown, especially that of Betula alleghaniensis Britt. Acer saccharum Marsh, continued to dominate the relatively unaffected sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 18 publications
2
54
0
Order By: Relevance
“…Furthermore, based on the successional status and shadetolerance rankings of AS and BA, several authors have concluded that BA should be initially favoured by large disturbances [18,40], and later replaced by AS [21,49]. Our results suggest the opposite, especially in the southern landscape.…”
Section: Speciessupporting
confidence: 41%
“…Furthermore, based on the successional status and shadetolerance rankings of AS and BA, several authors have concluded that BA should be initially favoured by large disturbances [18,40], and later replaced by AS [21,49]. Our results suggest the opposite, especially in the southern landscape.…”
Section: Speciessupporting
confidence: 41%
“…In general, small canopy gaps may fill in quickly with existing canopy tree species following catastrophic wind disturbance, yet larger gaps rely on existing seed sources as well as introduced seeds for regeneration of trees [33] . The amount of debris on the ground is an issue, however.…”
Section: Hardwoods and Cypress Swampsmentioning
confidence: 99%
“…Dunn et al [33] investigated the regeneration process of an old-growth hemlock-hardwood forest in New Hampshire following a catastrophic blowdown. The 1977 post-blowdown sample was compared to preblowdown datasets from 1967.…”
Section: Hardwoods and Cypress Swampsmentioning
confidence: 99%
“…By the early 1930s foresters began to take note of this loss and inventories of remnants were conducted, for example, in Pennsylvania (Lutz 1930 a, b;Hough 1936). Several authors have since described other small relict stands scattered throughout the Northeast (e.g., Stearns 1949, Dunn et al 1983, Gore and Patterson 1986. Apart from these small relicts there are several larger remnants in the Upper Peninsula of Michigan within which only very limited logging has occurred (Lorimer and Frelich 1994).…”
Section: The Northern Hardwood Forestmentioning
confidence: 99%
“…The larger gaps from windthrow occur as a result of two types of storms, "downbursts" and tornadoes. Downbursts are a type of severe thunderstorm (Fujita 1978, Dunn et al 1983 and are a more common cause of stand destruction than tornadoes but produce smaller openings (Canham and Loucks 1984). Tornadoes are very rare.…”
Section: Dynamics Of Northern Hardwood Forestsmentioning
confidence: 99%